WIVES’ RIGHT TO PURSUE A CAREER IN ISLAMIC FEMINISM: AN EPISTEMOLOGICAL ANALYSIS OF GENDER JUSTICE IN CONTEMPORARY RELIGIOUS DISCOURSE - Pratama, Andhika; Fatimah, Siti; Mahfud; Qeis Aimar (Universitas Islam Indonesia, 2026)
Purpose – This article aims to conduct a comparative analysis of the epistemology of gender justice in the thoughts of Husein Muhammad and Faqihuddin Abdul Kodir, particularly in formulating the theological and ethical legitimacy of women's rights to pursue a career after marriage, as well as assessing the contribution of both their thoughts to the renewal of religious understanding in Indonesia. Methods – This study used a comparative approach to the thoughts of Husein Muhammad and Faqihuddin Abdul Kodir and a comparative epistemology. Primary data were obtained from the works of these two figures. Secondary data were obtained from relevant sources. The data were analyzed through a critical reading of the epistemological approach, argumentation patterns, and normative implications of each thought. Findings – The study found that both figures affirm women's right to a career as part of the principles of justice and reciprocity in Islam but through different epistemological paths. Husein Muhammad emphasizes historical-epistemological criticism of patriarchal fiqh constructions, while Faqihuddin Abdul Kodir develops the mubādalah methodology as an applicable relational ethic. These differences do not negate each other, but rather enrich the plural and dynamic discourse of Islamic feminism. Both epistemologies have real transformative power when translated into family law discourse, public policy, and social practices in Indonesia, although their implementation still faces cultural resistance and regulatory structures that are not yet fully gender-responsive. Research contribution/limitations – This research contributes to the provision of a theoretical and argumentative framework that can be used to formulate a discourse of moderate gender justice rooted in the Islamic intellectual tradition.